Audit fees, audit quality, and auditor performance: Insights from Indonesian professionalism - Handoyo, Sigit; Febriani, Ninditya Wahyu (Jurnal Akuntansi dan Auditing Indonesia, 2025)
This study aims to analyze the factors that influence audit quality, namely the audit committee, audit tenure, audit fee, PAF (Public Accounting Firm) rotation, and client company size. The population in this study were all manufacturing companies on the Indonesia Stock Exchange for the 2019-2022 period and the sample of this study was 76 manufacturing companies that met the sample criteria during the study period. The sampling technique in this study used the purposive sampling method and used logistic regression to analyze. Based on the study, it can be concluded that the audit committee, audit tenure, and PAF rotation do not have an effect on audit quality. Meanwhile, audit fees and client company size have a positive effect on audit quality. This shows that large companies are able to pay high fees to auditors will obtain quality audit results. The implications of this study indicate that there is a tendency that auditors in Indonesia will work as well as possible if they get a promising fee, so it is necessary to emphasize to auditors the importance of a professional attitude that a professional's work does not only depend on the fee they get.